Good governance and territorial marketing - two sides of the same coin? Development of market orientation through governance mechanisms in local government. - Justyna Anders; Wawrzyniec Rudolf (European Regional Science Association (ERSA), 2011)
The scope of the paper is to discuss the role of good governance in improving responsiveness of local government to the needs of the selected target markets (investors, tourists, students). The criteria of good governance and governance indicators are analysed with regard of their applicability in building customer orientation of local authorities i.e. increasing market intelligence, disseminating knowledge about current and prospect users of the territory and fostering organizational culture conducive of gathering, sharing and applying market information for satisfying local demand. The objective is to assess usefulness of governance mechanisms in improving marketing management process (i.e. analysis, planning, implementation and control) of the local authorities towards selected groups of target customers (investors, tourists, students). The paper will create the analytical framework for the future research in selected Polish cities. The main good governance rules will be tested both from the governors' perspectives and from the customer one. The issues below should be taken into consideration n terms of governors' performance: focusing on the organisation's purpose and on outcomes for citizens and service users performing effectively in clearly defined functions and roles promoting values for the whole organisation and demonstrating the values of good governance through behaviour taking informed, transparent decisions and managing risk developing the capacity and capability of the governing body to be effective engaging stakeholders and making accountability real Different approaches to public service quality at the operational level and territorial marketing at the strategic level as well as methodologies of measuring governance will be taken into account as a theoretical background.
Keywords: 330